A Theoretical Review of Language and Moral Development According to Chomsky and Kohlberg - Surya Adinda, Amalia; Eva Latipah; Dewi Solikhatun; Bagus Zainur Rohman (Insight School Academy, 2025)
Introduction to The Problem: This article theoretically explores two main pillars of human developmental psychology: language and moral development. It is based on the need for a comprehensive review that separately outlines Noam Chomsky's transformational generative theory of language development and Lawrence Kohlberg's stages of moral development theory. Purpose: This study provides an in-depth and separate intellectual profile, postulates and theoretical structure, as well as the dynamics of the language and moral development processes of each theory. Design/methods/approach: Through a literature study method with a psychological approach, this study analyzes and synthesizes relevant literature to build a clear understanding of the basic assumptions and implications of both theories. The researcher analyzed various primary and secondary sources from various academic databases. The data collected were analyzed using content analysis techniques. Findings: The results of the study indicate that, although Chomsky and Kohlberg operate in different domains with unique theoretical assumptions, both have made fundamental contributions to shaping our understanding of how individuals develop their language and moral capacities separately. Originality/value: The novelty of this article is that it provides a structured theoretical review focused on each theory independently, without comparison or synthesis, thereby establishing a strong foundation of understanding before more complex interconnection studies.